(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The integration of technology in education has brought numerous benefits to the learning process. Technology enhances engagement, personalizes learning experiences, and equips students with crucial digital skills. Despite concerns about distractions and unequal access, technology's overall impact on education is positive. Tools like interactive platforms and virtual classrooms create dynamic learning environments. Technology has become essential part of modern education. The integration of technology in educational settings has sparked a debate on its efficacy and impact on the learning process. Supporters argue that technology enhances engagement, facilities personalized learning, equips students with essential digital skills for future. From learning platforms to online classrooms, technology offers unprecedented opportunities to create dynamic and interactive learning environments. However, detractors raise concerns about the potential for distraction, unequal access to technology and education indicates a complex landscape where both challenges and opportunities coexist, shaping the way we approach teaching and learning in the digital age